A Rare Case of Schwannoma in the Lateral Sural Cutaneous Nerve: Diagnosis, Surgical Intervention, and Clinical Outcomes - Vidhyadhar Wadkar; PN Kulkarni (Journal of Neonatal Surgery, 2024)
Peripheral nerve sheath tumors (PNSTs) are uncommon, with schwannomas being the most frequent benign variant. These tumors, composed solely of Schwann cells, typically arise in the head, neck, or upper extremities, making their occurrence in the lower limbs, especially in the sural nerve, extremely rare. This case report documents a schwannoma in the lateral sural cutaneous nerve of a 51-year-old female presenting with pain and swelling in the right ankle. Diagnostic imaging with MRI revealed a well-defined, encapsulated mass with characteristic features of schwannoma, confirmed through histopathology. Surgical excision using microscopic enucleation was performed, preserving nerve function and resulting in complete symptom relief. Postoperative follow-up showed no recurrence or neurological deficits. This case highlights the importance of considering schwannomas in differential diagnoses of lower limb masses and demonstrates that precise surgical intervention can yield excellent outcomes.